Evaluation of The Nuclear Data on(Î±,n)Reaction for Natural Molybdenum - Hamadani, H.M.T.; Younis, T.A.; Ebrahiem, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The cross section evaluation for (Î±,n) reaction was calculated according to the available International Atomic Energy Agency (IAEA) and other experimental published data . These cross section are the most recent data , while the well known international libraries like ENDF , JENDL , JEFF , etc.   We considered an energy range from threshold to 25 MeV in interval (1 MeV).   The average weighted cross sections for all available experimental and theoretical(JENDL) data and for all the considered isotopes was calculated . The cross section of the element is then calculated according to the cross sections of the isotopes of that element taking into account their abundance . A mathematical representative equation for each of the element and their isotopes are "formulated" they represent the variation of the cross section with energy . The evaluated  (Î±,n)  cross sections which was used to calculate the neutron yield for (Mo) for the first time ,which are very important in nuclear technology .